2000
DOI: 10.1046/j.1464-410x.2000.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen and ageing on gene expression of vasoactive intestinal polypeptide in rat corpus cavernosum

Abstract: Objective To clarify the effects of androgens (testosterone and dihydrotestosterone, DHT) and ageing on gene expression of vasoactive intestinal polypeptide (VIP), assessed as the expression of VIP mRNA, in rat corpus cavernosum. Materials and methods The study comprised 160 male Sprague Dawley rats divided into group A (56 rats, 5 weeks old), group B (50 rats, 10 weeks old) and group C (54 rats, 58 weeks old). Groups A±C were subdivided, respectively, into subgroups 1 (intact controls), 2 (castrated), 3 (cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Andersen et al (2002) reported that free testosterone levels in Wistar rats decreased from 3 to 22 months in Wistar rats, but no intermediate ages were studied. Shen et al (2000) found that free testosterone concentrations were similar in Sprague-Dawley rats at 2- and 13-months of age, similar to our current results. Thus, future studies would help to resolve some differences in results.…”
Section: Discussionsupporting
confidence: 91%
“…Andersen et al (2002) reported that free testosterone levels in Wistar rats decreased from 3 to 22 months in Wistar rats, but no intermediate ages were studied. Shen et al (2000) found that free testosterone concentrations were similar in Sprague-Dawley rats at 2- and 13-months of age, similar to our current results. Thus, future studies would help to resolve some differences in results.…”
Section: Discussionsupporting
confidence: 91%
“…The T and DHT levels in castrated rats and the DHT level in finasteride‐treated groups were significantly lower than those in the control group. In the castrated animals, there was a high degree of fibrosis in the corpus cavernosum with irregularly arranged collagenous fibers and a marked decrease in smooth muscle fibers, while in the DHT‐inhibited group (finasteride‐treated), the corpus cavernosum comprised a substantial amount of thick and irregularly arranged collagenous fibers, but the degree of fibrosis was less than that of the castration group (Shen et al, 2000). This work suggests that because finasteride inhibits the action of DHT but not T on the corporal cavernosal tissue, the degree of fibrosis was less in the DHT‐inhibited group than in the castration group.…”
Section: Deficiency In 5 α‐Reductasementioning
confidence: 90%
“…The test tubes were sealed and placed in a water bath (80°C) for 2 h. After that, the samples were cooled to room temperature, and 5 ml of potassium carbonate solution (7%) was added to the reaction mixture. The mixture was then Serum concentrations of E2, DHT, aminotransferase, and serum static lipid profi le Serum E2 and DHT were measured as described in previous studies ( 28,29 ). Serum lipid parameters were measured with a lipidmeasuring kit (Wako Pure Chemical Industries Ltd, Osaka, Japan) according to the protocol provided with kit.…”
Section: Measurement Of Static Levels Of Fatty Acids From Liver Usingmentioning
confidence: 99%